Robustness of Momentum-Indirect Interlayer Excitons in MoS2/WSe2 Heterostructure against Charge Carrier Doping - Khestanova, Ekaterina; Ivanova, Tatyana; Gillen, Roland; D'Elia, Alessandro; Lacey, Oliver Nicholas Gallego; Wysocki, Lena; Grueneis, Alexander; Kravtsov, Vasily; Strupinski, Wlodek; Maultzsch, Janina; Kandyba, Viktor; Cattelan, Mattia; et al. (ACS Photonics, 2022)
Monolayer transition-metal dichalcogenide (TMD) semiconductors exhibit strong excitonic effects and hold promise for optical and optoelectronic applications. Yet, electron doping of TMDs leads to the conversion of neutral excitons into negative trions, which recombine predominantly nonradiatively at room temperature. As a result, the photoluminescence (PL) intensity is quenched. Here we study the optical and electronic properties of a MoS2/WSe2 heterostructure as a function of chemical doping by Cs atoms performed under ultrahigh vacuum conditions. By PL measurements, we identify two interlayer excitons and assign them to the momentum-indirect Q-Γ and K-Γ transitions. The energies of these excitons are in very good agreement with ab initio calculations. We find that the Q-Γ interlayer exciton is robust to the electron doping and is present at room temperature even at a high charge carrier concentration (∼1013 cm-2). Submicrometer angle-resolved photoemission spectroscopy (μ-ARPES) reveals a charge transfer from deposited Cs adatoms to both the upper MoS2 and the lower WSe2 monolayers without changing the band alignment. This leads to a small (∼10 meV) energy shift of interlayer excitons. Robustness of the momentum-indirect interlayer exciton to charge doping opens up an opportunity for using TMD heterostructures in light-emitting devices that can work at room temperature at high densities of charge carriers.
CRIS-Team Scopus Importer:2023-03-27
Keywords: alkali metal-doped TMDs; clean TMD heterobilayer; indirect excitons in WSe; photoluminescence in doped TMD heterobilayers; Γ-Q exciton in WSe